Chemical speciation of phosphorus in surface sediments from the Jiangsu Coast, East China: Influences, provenances and bioavailabilities. (February 2021) - Mao, Changping; Li, Tianning; Rao, Wenbo; Tang, Zhen; Song, Yinxian; Wang, Shuai
Abstract: Sixty-one surface sediment samples collected from the Jiangsu Coast (JSC), East China were investigated to explore the influences, provenances and bioavailabilities of P species. Authigenic and detrital P fractions were the dominant species, accounting for 28.53% and 44.04% of the total P content, respectively. Exchangeable, Fe-bound and organic P fractions were biologically available, with an average total of 5.94 μmol/g; this value was governed by grain sizes and the organic matter and carbonate contents. Exchangeable and organic P fractions were transformed between each other, while contributing to the formation of Fe-bound and authigenic P. Phosphorus in the JSC sediments originated mainly from the Yellow River. The unique distribution pattern of P species in the JSC depends on P sources and local environments. These findings improve our understanding of the P cycle and eutrophication in the Jiangsu Coastal Zone. Highlights: Detrital P is the most abundant, followed by authigenic P in the coastal sediments. P came chiefly from the Yellow River rather than the Yangtze River. Exchangeable P and organic P are the two most dominant P pools for biological use.